Value chain prioritization and development in India: Are national and state-level priorities aligned? - Pal, Barun Deb; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2024)
Presented at 32nd ICAE conference 2024, NASC Complex, New Delhi, India, August 2-7, 2024.